Tofacitinib treatment of systemic juvenile idiopathic arthritis: a case report and literature review - Zhu, Meifang; Zhao, Yan; Zhang, Xiaohua; Zhou, Peng; Jin, Jing; Fan, Zhidan; Yu, Haiguo (Frontiers in Pediatrics, 2025)
ObjectiveSystemic juvenile idiopathic arthritis (sJIA), a particularly aggressive form of childhood arthritis, is characterized by persistent systemic inflammation. The most advanced treatments include biologic agents that target the interleukin-1(IL-1) and interleukin-6(IL-6) pathways. However, sJIA continue to pose challenging challenges for rheumatologists treating pediatric patients worldwide.Methods1 children with sJIA was retrospectively collected from the Department of Rheumatology and immunology, Children's Hospital of Nanjing Medical University, Nanjing. Literature published between 2019 and 2024 was reviewed to understand the effect of tofacitinib on patients with sJIA.ResultsAfter a month of treatment of tofacitinib, there was a significant improvement in clinical symptoms and inflammatory indicators showed a marked decrease. As of July 2023, the patient's condition was effectively in remission. The efficacy of tofacitinib treatment was remarkable.ConclusionTofacitinib has shown good efficacy and safety in the treatment of sJIA patients, effectively controlling disease activity and relieving symptoms. The application of Janus kinase (JAK) inhibitors may offer a new treatment option for this disease.